Effect of Exercises rate Running In 1500 m and 3000 m Pace with different Percentages In improved in the enzyme LDH and the speed reserve and - Dr. Ahmed Murtadha; Dr. Saif Sabbar; Dr. Khalid Mohammed; M. Baida Khudhur (الرياضة المعاصرة)
In spite of what has been achieved in the scientific progress in the field of sports achievement, it is necessary to continue to conduct more research, studies and experiments to increase knowledge and expand the scientific facts and link them to reach the best methods and methods of training to develop each game of sports and each according to its specificity and in an optimal manner in an attempt to invest Existing human energies to the maximum extent possible.